PENGARUH PRIBADI, SOSIAL, DAN BUDAYA TERHADAP KEPUTUSAN MEMILIH PEMBIAYAAN PENSIUN PADA BANK SYARIAH MANDIRI KC SUMBERREJO-BOJONEGORO (GEMA EKONOMI, 2019)
In Bojonegoro there are conventional and sharia banks that both have financing or credit products for pensioners. This led to competition in obtaining the customer to elect retirement financing at Bank Syariah Mandiri. Banking should thoroughly understand the factors affecting the decision of the customer in choosing financing. The goal that is to be achieved in this study is to know the individual, social, and cultural influences both partially and simultaneously on the decision to choose pension financing in Bank Syariah Mandiri KC Sumberrejo and toretrieve the most dominant variable. This study is quantitative research using the Survey method. Specifies the number of samples with the Slovin formula and the sampling technique used is Simple Random Sampling. The collection of data is done by spreading the questionnaire to 78 respondents with the criteria of having pension financing at Bank Syariah Mandiri KC Sumberrejo. Data analysis using multiple linear regression analyses. The results showed that the simultaneous personal, social and cultural effect was significant to the decision to choose the certification financing at Bank Syariah Mandiri KC Sumberrejo based on the value F calculate > F table (7, 943 > 2.73) as well as the significance sig value 0,000 < 0.05 (Alpha). Partial personal factors have a significant effect on the decision to choose the certification financing based on the calculated T value > of T table (3,759 > 1,991) and the value of sig significance 0,000 < 0.05 (Alpha). Social factors have no significant effect on the decision to choose the certification financing based on the calculated T value < of T table (-1.084 > 1,991) and the significance value of sig 0.282 > 0.05 (Alpha). Cultural factors have significant effect on the decision to choose the certification financing based on the calculated T value > of T table (2,811 > 1,991) and the value of sig significance 0,006 < 0.05 (Alpha). Personal variables the most dominant influence on the decision to choose a pension financing in Bank Syariah Mandiri KC Sumberrejo.DOI 10.5281/zenodo.3629907